Platelet-Activating Biominerals Enhanced Injectable Hydrogels With Superior Bioactivity for Bone Regeneration - Chen, Xin; Yan, Jiajun; Jiang, Yingying; Fan, Yunshan; Ying, Zhengran; Tan, Shuo; Zhou, Zhi; Liu, Junjian; Chen, Feng; He, Shisheng (Frontiers in Bioengineering and Biotechnology, 2022)
Refractory bone fracture, which is difficult to be treated, is a common clinical disease. Taking inspiration from the natural process of bone regeneration, we provide a biomimetic strategy to develop a new injectable biomaterial for repairing bone defects, which is mainly composed of platelets, fibrins, and biominerals. Biomineral nanoparticles (EACPNs) with an amorphous phase are prepared by an enzyme-catalyzed route and display a platelet-activating property. The composite hydrogel (EPH) of EACPNs, fibrins, and platelets is injectable, and has similar chemical properties to natural materials in bone regeneration. The dried EPH samples display a highly porous structure, which would be favorable for cell attachment and growth. The results from in vitro studies indicate that EPH has high biocompatibility and superior bioactivity in promoting the osteogenic differentiation of rat bone marrow stem cells (rBMSCs). Furthermore, the results from in vivo studies clearly indicate that EPH can induce the formation of new collagen and vessels in the defect area, thus leading to faster regeneration of bone defects at 2 weeks. Our study provides a strategy for designing new biomimetic materials, which may be favorable in the treatment of refractory bone fracture.